2015
DOI: 10.1016/j.pnpbp.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic system dysfunction in mood disorders: a key target for developing improved therapeutics

Abstract: Uric acid and purines (such as adenosine) regulate mood, sleep, activity, appetite, cognition, memory, convulsive threshold, social interaction, drive, and impulsivity. A link between purinergic dysfunction and mood disorders was first proposed a century ago. Interestingly, a recent nationwide population-based study showed elevated risk of gout in subjects with bipolar disorder (BD), and a recent meta-analysis and systematic review of placebo-controlled trials of adjuvant purinergic modulators confirmed their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
91
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 196 publications
1
91
0
1
Order By: Relevance
“…Uric acid has been linked with a variety of psychological conditions, including neurodegenerative conditions and emotion-related psychopathology (Albert et al, 2015; Bowman et al, 2010; Fang et al, 2013; Jahangard et al, 2014; Kesebir et al, 2014; Lyngdoh et al, 2013; Machado-Vieira et al, 2008). Although variations in uric acid level alters neural transmission (Ortiz et al, 2015; Ozten et al, 2015), the brain functions that link uric acid and mental health have yet to be determined. The current study found a positive relationship between bilateral hippocampal complex activity and uric acid concentrations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Uric acid has been linked with a variety of psychological conditions, including neurodegenerative conditions and emotion-related psychopathology (Albert et al, 2015; Bowman et al, 2010; Fang et al, 2013; Jahangard et al, 2014; Kesebir et al, 2014; Lyngdoh et al, 2013; Machado-Vieira et al, 2008). Although variations in uric acid level alters neural transmission (Ortiz et al, 2015; Ozten et al, 2015), the brain functions that link uric acid and mental health have yet to be determined. The current study found a positive relationship between bilateral hippocampal complex activity and uric acid concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Although imbalanced uric acid levels have a long-standing link with medical conditions such as gout, uric acid also affects the central nervous system. For example, increased uric acid levels accelerate purine transformation, leading to alterations of neural transmission (Ortiz et al, 2015; Ozten et al, 2015). Additionally, uric acid has been linked with neurodegenerative conditions, such as Alzheimer’s, Parkinson’s, and Huntington’s disease, as well as Multiple Sclerosis and mild cognitive impairment (MCI) associated with aging (Bowman et al, 2010; Fang et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical and preclinical studies have demonstrated the involvement of purinergic system in psychiatric disorders including MDD [6][7][8]. Accordingly, adenosine receptors are able to control cellular excitability and modulate several neurotransmission systems involved in behavioral, neurochemical, and endocrine alterations associated with MDD, such as dopaminergic, serotoninergic, and glutamatergic systems [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The purinergic system has been linked to the etiology of mood disorders via alterations in ATP and adenosine signaling as well as through inherited patterns and the neuroinflammatory hypothesis (for review, see Ortiz et al, 2015). It is known that adenosine signaling has a neuromodulatory role, which is involved in the regulation of important mechanisms in the CNS, such as anxiety states (Csölle et al, 2013), sleep (Huang et al, 2011;Carús-Cadavieco and de Andrés, 2012), motor function, cognition and memory (Salamone and Correa, 2009;Shen et al, 2012;Wei et al, 2011), among others.…”
Section: Introductionmentioning
confidence: 99%